High-transmittance and high-performance polyurethane protective material and its preparation method and application
Through a two-component raw material system, combined with polyester polyol and symmetric aromatic diisocyanate PPDI, the existing polyurethane sole materials have poor transparency and insufficient mechanical properties, and achieved high transparency, excellent mechanical properties and good hydrolysis resistance, meeting the market's demand for high transparency, high strength and high wear resistance.
Patent Information
- Application Number
- CN202411611935.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing polyurethane sole materials have problems such as poor transparency, insufficient mechanical properties, poor hydrolysis resistance and short service life, which are difficult to meet the market's demand for high transparency, high strength and high wear resistance.
Using a two-component raw material system, component A includes polyester polyol, small molecule polyol, catalyst, anti-hydrolyzer and anti-aging agent, component B includes liquid polyester polyol and symmetric aromatic diisocyanate PPDI, which improves the transparency, mechanical properties and hydrolysis resistance of the material through synergistic action.
It has achieved high transparency, excellent mechanical properties, good wear resistance and hydrolysis resistance. The hardness, rebound rate, wear, tensile strength and light transmittance of the product have reached high standards, meeting the demand of the sole market.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polyurethane protective materials, and specifically relates to a high-transmittance and high-performance polyurethane protective material and a preparation method and application thereof. Background Art
[0002] As people yearn for a better life and pay more attention to their own health, more and more people are joining outdoor sports. As a result, people have higher requirements for the comfort and elasticity of footwear products. The soles should not only be beautiful, but also safe and comfortable. At present, the sole materials are mainly divided into plastic soles, rubber soles and polyurethane soles. Among them, polyurethane soles have been widely used because they solve the problems of easy breaking of plastic soles and easy debonding of rubber soles in China.
[0003] Polyurethane soles are mainly made by polyester-micro-foaming process. Compared with polyether soles, polyester soles have the advantages of tear resistance, oil resistance, solvent resistance and good adhesion, but their hydrolysis resistance is poor, which makes the soles prone to cracking and breaking. Micro-foaming process soles are light, soft and elastic, but their wear resistance and mechanical properties are poor, which makes the soles easy to damage and have a short service life. In addition, the products are generally opaque in appearance and poor in controllability, which makes it difficult to meet people's current demand for the beauty of sole products.
[0004] CN118165209A discloses an elastomeric material for soles and a preparation method thereof, which uses polyester polyol as a raw material, uses aliphatic and alicyclic isocyanates, and works synergistically with fillers. The silicon dioxide and titanium dioxide contained in the filler improve the anti-yellowing performance of the matrix and the wear resistance of the matrix. However, the preparation process of the filler used is particularly complicated, and the time and energy consumption required for the preparation are high. At the same time, a foaming process is used, and the sole material produced is an opaque product with poor controllability.
[0005] CN117106154A discloses a low-temperature and dirt-resistant polyurethane sole resin and its preparation method and application. The polyurethane sole resin is mainly prepared by using polyester polyol, polyester polymer polyol and polyether polyol as raw materials, and then adding terminal hydroxyl siloxane, chain extender, foaming agent, catalyst, foaming agent, isocyanate and other substances to obtain the polyurethane sole resin, which is applied to the sole. By introducing the siloxane structure, the sole has better low-temperature elasticity. However, the preparation method using the foaming process has the disadvantages of opacity and poor mechanical properties, and its tensile strength is only 5.5MPa.
[0006] Therefore, it is necessary to develop a polyurethane sole protective material with high transparency, excellent mechanical properties, long service life and high comfort. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art, provide a high-transparency and high-performance polyurethane protective material, the product has excellent mechanical properties, high transparency, strong resilience, and good wear resistance and hydrolysis resistance, and is applied to the outer layer of a rubber sole as a sole protective material to protect the sole or directly applied to the outer sole and midsole of the sole material, meeting the demand of the sole market for high-transparency, high-strength, and high-wear-resistant polyurethane protective materials. The present invention also provides a preparation method thereof.
[0008] The high-transmittance and high-performance polyurethane protective material of the present invention is composed of component A and component B in a mass ratio of 100:(128-247), wherein component A includes the following raw materials in mass parts: 90.7-95.8 parts of polyester polyol 1, 2.2-7.3 parts of small molecule polyol, 0.5-1.3 parts of catalyst, 0.2-0.6 parts of anti-hydrolysis agent, and 0.4-0.8 parts of anti-aging agent;
[0009] Component B includes the following raw materials in parts by mass: 78.8-83.4 parts of polyester polyol 2 and 16.6-21.2 parts of diisocyanate.
[0010] The polyester polyol 1 is prepared by the alkyd condensation reaction of a polyol having an even number of carbon atoms and ≥4 carbon atoms and adipic acid, has a number average molecular weight of 1000-2000, and a moisture content of ≤0.03%, and is preferably one or two of PE-4010, PE-6010, and PE-4020.
[0011] The polyester polyol 2 is a liquid polyester polyol with a number average molecular weight of 1500-2000 and a moisture content of ≤0.03%, preferably one or two of PE-2420, PE-2415, PE-2520, and PE-8020.
[0012] The small molecule polyol is one or two of INOVOL C304, trimethylolpropane (TMP), methyl propanediol (MPO), and trimethylolethane (TME).
[0013] The catalyst is one or two of an organic bismuth catalyst BCAT-20A, an environmentally friendly catalyst CUCAT-RM01, and an amine catalyst DXD-07C.
[0014] The anti-hydrolysis agent is HyMax ® 220. HyMax ® One or both of 1010.
[0015] The anti-aging agents are CHISORB 971 and Sunok ® 1076A mixture in any proportion.
[0016] The diisocyanate is a symmetrical aromatic diisocyanate: p-phenylene diisocyanate (PPDI).
[0017] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0018] (1) Component A: Evenly mix polyester polyol 1, small molecule polyol, catalyst, anti-hydrolysis agent and anti-aging agent at 40-60°C to obtain component A;
[0019] (2) Component B: Add polyester polyol 2 into a reaction kettle, start stirring, add diisocyanate, and then seal the kettle with nitrogen. Maintain the temperature at 55-60°C for 30-40 minutes, and then continue to heat the reaction. After the reaction is completed, maintain the vacuum degree ≤-0.095MPa to remove bubbles, and prepare a polyurethane prepolymer with an isocyanate content of 5.0-7.0%, i.e., component B;
[0020] (3) When in use, mix component A and component B evenly according to the mass ratio, pour into a mold at 70-85°C, open the mold after 10-15 minutes, and leave it at room temperature for 12-16 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0021] In the step (2), the temperature is raised to 75-85°C in the first 60 minutes, and the reaction time at 75-85°C is 1-3 hours.
[0022] In the step (3), when component A and component B are mixed uniformly according to the mass ratio, the mixing temperature is 60-80°C.
[0023] The application of the high-transmittance and high-performance polyurethane protective material is to apply it to sole protective materials.
[0024] The present invention adopts a two-component raw material system. Component A adopts polyester polyol with lower ester bond density, so that the prepared elastomer exhibits higher resilience when subjected to impact, and is matched with a small molecule polyol with higher cross-linking degree of side methyl side chains to protect the ester bond from OH. - It attacks the surface of the molecules while hindering the formation of intermolecular crystallization, thereby improving the hydrolysis resistance of the product and making the product highly transparent. Secondly, a symmetrical aromatic diisocyanate PPDI is selected in component B, and its structural regularity and polarity are used to improve the wear resistance, hydrolysis resistance and mechanical properties of the product. It is matched with low-crystalline liquid polyester polyols to improve the mechanical properties of the product while maintaining high transparency. Finally, under the synergistic effect of multiple specific components, an anti-hydrolysis agent and an anti-aging agent are combined to prepare a highly transparent and high-performance polyurethane protective material.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The high-transmittance and high-performance polyurethane protective material of the present invention adopts symmetrical aromatic diisocyanate p-phenylene diisocyanate as component B. The compact and symmetrical molecular structure of the component greatly improves the mechanical properties and wear resistance of the product. At the same time, the high crystallinity of p-phenylene diisocyanate is balanced by the polyester polyol which is in liquid state at room temperature and has weak crystallinity, thereby ensuring that the product has high transparency and high resilience.
[0027] (2) The high-transmittance and high-performance polyurethane protective material of the present invention uses a small molecule polyol with a branched chain or a higher degree of cross-linking as a chain extender in component A, which improves the transparency of the product, and selects polyester polyols with a longer carbon chain and a lower ester bond density, so that the product has excellent rebound performance. The anti-hydrolysis agent and anti-aging agent components are synergistic, and the product has excellent hydrolysis resistance.
[0028] (3) The preparation method of the high-transmittance and high-performance polyurethane protective material of the present invention has a simple process and the prepared product has excellent comprehensive performance: the hardness of the Shore A reaches 66-69, the rebound is 60-69%, and the wear is ≤15mm 3 , minimum up to 10mm 3 ; Tensile strength ≥30MPa, up to 35MPa; Trouser-type tear strength ≥30kN / m, up to 37kN / m; Light transmittance ≥77%, up to 86%; Haze ≤1.2%, minimum 0.7%, applied to the outer layer of rubber soles as sole protective material or directly applied to the outsole and midsole of sole materials, meeting the sole market's demand for high-transparency, high-strength and high-wear-resistant polyurethane protective materials. DETAILED DESCRIPTION
[0029] The present invention is further described below with reference to Examples and Comparative Examples.
[0030] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.
[0031] Some of the raw materials used in the examples and comparative examples are described as follows:
[0032] PE-4010: number average molecular weight 1000, Shandong Yinuowei Polyurethane Co., Ltd.;
[0033] PE-6010: number average molecular weight 1000, Shandong Yinuowei Polyurethane Co., Ltd.;
[0034] PE-4020: number average molecular weight 2000, Shandong Yinuowei Polyurethane Co., Ltd.;
[0035] PE-2020: solid polyester polyol, number average molecular weight 2000, Shandong Yinuowei Polyurethane Co., Ltd.;
[0036] PE-2010: prepared by polycondensation of ethylene glycol and adipic acid, number average molecular weight 1000, Shandong Yinuowei Polyurethane Co., Ltd.
[0037] PE-2420: number average molecular weight 2000, Shandong Yinuowei Polyurethane Co., Ltd.;
[0038] PE-2520: number average molecular weight 2000, Shandong Yinuowei Polyurethane Co., Ltd.;
[0039] PE-8020: number average molecular weight 2000, Shandong Yinuowei Polyurethane Co., Ltd.;
[0040] PE-2415: number average molecular weight 1500, Shandong Yinuowei Polyurethane Co., Ltd.;
[0041] INOVOL C304: polyether polyol, number average molecular weight 375, Shandong INOVOL New Materials Co., Ltd.
[0042] TMP: Jiangxi Gaoxin Frontier Technology Co., Ltd.;
[0043] TME: Jiangxi Keding Chemical Materials Co., Ltd.;
[0044] MPO: Changlian Chemical (Panjin) Co., Ltd.;
[0045] PPDI: Zhejiang Lishui Youbang New Materials Co., Ltd.;
[0046] TDI: Shandong Yinuowei Polyurethane Co., Ltd.;
[0047] HyMax ® 220: Shanghai Langyi Functional Materials Co., Ltd.;
[0048] HyMax ® 1010: Shanghai Langyi Functional Materials Co., Ltd.;
[0049] CHISORB 971: Double Bond Chemical (Shanghai) Co., Ltd.;
[0050] Plastic ® 1076: Yantai Xinxiu Chemical Products Co., Ltd.;
[0051] CUCAT-RM01 catalyst: Guangzhou Yourun Synthetic Materials Co., Ltd.;
[0052] BCAT-20A catalyst: Guangzhou Yourun Synthetic Materials Co., Ltd.;
[0053] DXD-07C catalyst: Shandong Yinuowei Polyurethane Co., Ltd.
[0054] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0055] (1) Component A: Mix polyester polyol 1, small molecule polyol, catalyst, anti-hydrolysis agent and anti-aging agent at 40-60°C and stir evenly to obtain component A;
[0056] (2) Component B: Add polyester polyol 2 into a reaction kettle. When the temperature drops below 60°C, start stirring, add p-phenylene diisocyanate all at once, and then seal the kettle with nitrogen to maintain a slight positive pressure in the kettle. Keep the temperature at 55-60°C for 30-40 minutes, then continue to heat the reaction. In the first 60 minutes, heat to 75-85°C and keep it in this temperature range for 1-3 hours. After the reaction is completed, maintain a vacuum degree of ≤-0.095MPa to remove bubbles, and prepare a polyurethane prepolymer with an isocyanate content of 5.0-7.0%, i.e., component B.
[0057] (3) When in use, the mixing temperature is controlled at 60-80°C, component A and component B are mixed evenly at a mass ratio of 100:(128-247), poured into a mold at 70-85°C, the mold is opened after 10-15 minutes, and placed at room temperature for 12-16 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0058] Example 1
[0059] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0060] (1) Component A: 90.7 parts PE-6010 (water content ≤ 0.03%), 7 parts INOVOL C304, 1.3 parts CUCAT-RM01 catalyst, 0.3 parts anti-hydrolysis agent HyMax ® 220, 0.3 parts of anti-hydrolysis agent HyMax ® 1010, 0.2 parts of anti-aging agent CHISORB 971, 0.2 parts of anti-aging agent Sunok ® 1076 are mixed and stirred at 40°C to obtain component A;
[0061] (2) Component B: 80 parts of PE-8020 (water content ≤ 0.03%) were added to the reaction kettle. When the temperature dropped below 60°C, stirring was started, and 20 parts of PPDI were added at one time. The kettle was then sealed with nitrogen and a slight positive pressure was maintained in the kettle. The temperature was kept at 55°C for 30 minutes, and then the temperature was increased. The temperature was increased to 85°C within the first 60 minutes and kept for 1 hour. The vacuum degree was maintained at ≤-0.095 MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 7.0% was obtained, namely, component B.
[0062] (3) When in use, the mixing temperature is controlled at 60°C, component A and component B are mixed evenly in a mass ratio of 100:145, poured into a mold at 70°C, the mold is opened after 10 minutes, and left at room temperature for 16 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0063] Example 2
[0064] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0065] (1) Component A: 45 parts of PE-4010 (water content ≤ 0.03%), 47.7 parts of PE-6010 (water content ≤ 0.03%), 5 parts of INOVOL C304, 1.3 parts of CUCAT-RM01 catalyst, 0.4 parts of anti-hydrolysis agent HyMax ® 220, 0.2 parts of anti-aging agent CHISORB 971, 0.4 parts of anti-aging agent SUNOK ® 1076 are mixed and stirred at 50°C to obtain component A;
[0066] (2) Component B: 83.4 parts of PE-2520 (water content ≤ 0.03%) were added to the reaction kettle. When the temperature dropped below 60°C, stirring was started, and 16.6 parts of PPDI were added at one time. Then, the kettle was sealed with nitrogen and a slight positive pressure was maintained in the kettle. The temperature was kept at 60°C for 40 minutes, and then the temperature was increased. The temperature was increased to 80°C within the first 60 minutes and kept for 3 hours. The vacuum degree was maintained at ≤-0.095 MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 5.0% was obtained, namely, component B.
[0067] (3) When in use, the mixing temperature is controlled at 80°C, component A and component B are mixed evenly in a mass ratio of 100:193, poured into a mold at 85°C, the mold is opened after 15 minutes, and placed at room temperature for 14 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0068] Example 3
[0069] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0070] (1) Component A: 92 parts PE-4010 (water content ≤ 0.03%), 4.5 parts INOVOL C304, 1.5 parts MPO, 1 part DXD-07C catalyst, 0.2 parts anti-hydrolysis agent HyMax ® 1010, 0.4 parts of anti-aging agent CHISORB 971, 0.4 parts of anti-aging agent Sunok ® 1076 are mixed and stirred at 60°C to obtain component A;
[0071] (2) Component B: 40.4 parts of PE-8020 (water content ≤ 0.03%) and 40.4 parts of PE-2520 (water content ≤ 0.03%) were added to the reaction kettle. When the temperature dropped below 60°C, stirring was started, and 19.2 parts of PPDI were added at one time. Then, the kettle was sealed with nitrogen and a slight positive pressure was maintained in the kettle. The temperature was kept at 60°C for 30 minutes, and then the temperature was increased. The temperature was increased to 75°C within the first 60 minutes and kept for 2 hours. The vacuum degree was maintained at ≤-0.095 MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 6.5% was obtained, namely, component B.
[0072] (3) When in use, the mixing temperature is controlled at 80°C, component A and component B are mixed evenly in a mass ratio of 100:181, poured into a mold at 85°C, the mold is opened after 10 minutes, and placed at room temperature for 15 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0073] Example 4
[0074] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0075] (1) Component A: 94 parts PE-6010 (water content ≤ 0.03%), 4.5 parts TMP, 0.5 parts BCAT-20A catalyst, 0.4 parts anti-hydrolysis agent HyMax ® 220, 0.4 parts of anti-aging agent CHISORB 971, 0.2 parts of anti-aging agent SUNOK ® 1076 are mixed and stirred at 45°C to obtain component A;
[0076] (2) Component B: 83.4 parts of PE-2420 (water content ≤ 0.03%) were added to the reaction kettle. When the temperature dropped below 60°C, stirring was started, and 16.6 parts of PPDI were added at one time. Then, the kettle was sealed with nitrogen and a slight positive pressure was maintained in the kettle. The temperature was kept at 60°C for 40 minutes, and then the temperature was increased. The temperature was increased to 85°C within the first 60 minutes and kept for 2 hours. The vacuum degree was maintained at ≤-0.095 MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 5.0% was obtained, namely, component B.
[0077] (3) When in use, the mixing temperature is controlled at 65°C, component A and component B are mixed evenly in a mass ratio of 100:247, poured into a mold at 75°C, the mold is opened after 15 minutes, and placed at room temperature for 12 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0078] Example 5
[0079] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0080] (1) Component A: 95.8 parts of PE-4010 (water content ≤ 0.03%), 2.2 parts of TME, 0.3 parts of BCAT-20A catalyst, 0.7 parts of CUCAT-RM01 catalyst, 0.5 parts of anti-hydrolysis agent HyMax ® 220, 0.25 parts of anti-aging agent CHISORB 971, 0.25 parts of anti-aging agent Sunok ® 1076 are mixed and stirred at 50°C to obtain component A;
[0081] (2) Component B: 60 parts of PE-2420 (water content ≤ 0.03%) and 21.7 parts of PE-8020 (water content ≤ 0.03%) were added to the reaction kettle. When the temperature dropped below 60°C, stirring was started, and 18.3 parts of PPDI were added at one time. Then, the kettle was sealed with nitrogen and a slight positive pressure was maintained in the kettle. The temperature was kept at 55°C for 30 minutes, and then the temperature was increased. The temperature was increased to 85°C within the first 60 minutes and kept for 1.5 hours. The vacuum degree was maintained at ≤-0.095 MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 6.0% was obtained, namely, component B.
[0082] (3) When in use, the mixing temperature is controlled at 65°C, component A and component B are mixed evenly in a mass ratio of 100:176, poured into a mold at 75°C, the mold is opened after 10 minutes, and placed at room temperature for 16 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0083] Example 6
[0084] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0085] (1) Component A: 95.5 parts PE-4010 (water content ≤ 0.03%), 2.5 parts MPO, 1 part DXD-07C catalyst, 0.5 parts anti-hydrolysis agent HyMax ® 1010, 0.25 parts of anti-aging agent CHISORB 971, 0.25 parts of anti-aging agent Sunok ® 1076 are mixed and stirred at 60°C to obtain component A;
[0086] (2) Component B: 81.7 parts of PE-2420 (water content ≤ 0.03%) were added to the reactor. When the temperature dropped below 60°C, stirring was started, and 18.3 parts of PPDI were added at one time. Then, the reactor was sealed with nitrogen, and a slight positive pressure was maintained in the reactor. The temperature was kept at 55°C for 30 minutes. Then the temperature was raised to 85°C within the first 60 minutes, and the temperature was kept for 1.5 hours. The vacuum degree was maintained at ≤-0.095MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 6.0% was obtained, namely, component B;
[0087] (3) When in use, the mixing temperature is controlled at 65°C, component A and component B are mixed evenly in a mass ratio of 100:191, poured into a mold at 75°C, the mold is opened after 10 minutes, and left at room temperature for 12 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0088] Example 7
[0089] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0090] (1) Component A: 60 parts PE-6010 (water content ≤ 0.03%), 31.2 parts PE-4020 (water content ≤ 0.03%), 7.3 parts INOVOL C304, 0.5 parts BCAT-20A catalyst, 0.3 parts anti-hydrolysis agent HyMax ® 220, 0.2 parts of anti-hydrolysis agent HyMax ® 1010, 0.3 parts of anti-aging agent CHISORB 971, 0.2 parts of anti-aging agent Sunok ® 1076 are mixed and stirred at 40°C to obtain component A;
[0091] (2) Component B: 63.6 parts of PE-8020 (water content ≤ 0.03%) and 15.9 parts of PE-2415 (water content ≤ 0.03%) were added to the reaction kettle. When the temperature dropped below 60°C, stirring was started, and 20.5 parts of PPDI were added at one time. Then, the kettle was sealed with nitrogen and a slight positive pressure was maintained in the kettle. The temperature was kept at 55°C for 30 minutes, and then the temperature was increased. The temperature was increased to 85°C within the first 60 minutes and kept for 1 hour. The vacuum degree was maintained at ≤-0.095 MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 7.0% was obtained, namely, component B.
[0092] (3) When in use, the mixing temperature is controlled at 60°C, component A and component B are mixed evenly in a mass ratio of 100:128, poured into a mold at 70°C, the mold is opened after 10 minutes, and placed at room temperature for 16 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0093] Example 8
[0094] The method for preparing the high-transmittance and high-performance polyurethane protective material comprises the following steps:
[0095] (1) Component A: 92 parts PE-4020 (water content ≤ 0.03%), 6 parts TMP, 1 part DXD-07C catalyst, 0.5 parts anti-hydrolysis agent HyMax ® 1010, 0.25 parts of anti-aging agent CHISORB 971, 0.25 parts of anti-aging agent Sunok ®1076 are mixed and stirred at 50°C to obtain component A;
[0096] (2) Component B: 78.8 parts of PE-2415 (water content ≤ 0.03%) were added to the reaction kettle. When the temperature dropped below 60°C, stirring was started, and 21.2 parts of PPDI were added at one time. Then, the kettle was sealed with nitrogen and a slight positive pressure was maintained in the kettle. The temperature was kept at 55°C for 30 minutes, and then the temperature was increased. The temperature was increased to 80°C within the first 60 minutes and kept for 2 hours. The vacuum degree was maintained at ≤-0.095 MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 6.5% was obtained, namely, component B.
[0097] (3) When in use, the mixing temperature is controlled at 60°C, component A and component B are mixed evenly in a mass ratio of 100:149, poured into a mold at 70°C, the mold is opened after 15 minutes, and placed at room temperature for 14 hours to obtain a high-transmittance and high-performance polyurethane protective material.
[0098] Comparative Example 1
[0099] (1) Component A and its preparation process are the same as those in Example 5;
[0100] (2) Component B: 58.9 parts of PE-2420 (water content ≤ 0.03%) and 21.3 parts of PE-8020 (water content ≤ 0.03%) were added to the reaction kettle. When the temperature dropped below 60°C, stirring was started and 19.8 parts of TDI were added at one time. Then, the kettle was sealed with nitrogen and a slight positive pressure was maintained in the kettle. The reaction was allowed to release heat naturally for 30 minutes and then the temperature was raised. The temperature was raised to 87°C within the first 90 minutes and kept at this temperature for 3 hours. The vacuum degree was maintained at ≤ -0.095 MPa to remove bubbles, thereby obtaining a polyurethane prepolymer with an isocyanate content of 6.0%, i.e., component B.
[0101] (3) When in use, the mixing temperature is controlled at 65°C, component A and component B are mixed evenly in a mass ratio of 100:176, poured into a mold at 75°C, the mold is opened for 10 minutes, and the polyurethane protective material is obtained by placing it at room temperature for 16 hours.
[0102] Comparative Example 2
[0103] This comparative example 2 is the same as example 6, except that PE-4010 in component A is replaced with PE-2010 of the same mass fraction, and the remaining steps are the same.
[0104] Comparative Example 3
[0105] This comparative example 3 is the same as example 4, except that the TMP in component A is replaced with 1,4-butanediol (BDO) of the same mass fraction, and the remaining steps are the same.
[0106] Comparative Example 4
[0107] This comparative example is the same as Example 2, except that PE-2520 in component B is replaced with PE-2020 of the same mass fraction, and the remaining steps are the same.
[0108] Comparative Example 5
[0109] (1) Component A: 92 parts PE-4010 (water content ≤ 0.03%), 4.5 parts INOVOL C304, 1.5 parts MPO, 1 part DXD-07C, 0.5 parts anti-aging agent CHISORB 971, 0.5 parts anti-aging agent SUNOK ® 1076 are mixed and stirred at 60°C to obtain component A;
[0110] (2) Component B and its preparation process are the same as those in Example 3;
[0111] (3) When in use, the mixing temperature is controlled at 80°C, component A and component B are mixed evenly in a mass ratio of 100:181, poured into a mold at 85°C, opened after 10 minutes, and left at room temperature for 15 hours to obtain the polyurethane protective material.
[0112] The performance of the polyurethane protective materials prepared in Examples 1-8 and Comparative Examples 1-5 was tested respectively, and the test standards and methods were as follows: The transmittance and haze of the product were measured using the SGW-810 haze transmittance meter of Guangzhou Packaging Equipment Co., Ltd. The test conditions were as follows: After the machine was turned on and preheated for 20 minutes, at room temperature, a 2 mm thick sample sheet was placed in the colorimeter and fixed with a positioning clip so that it was close to the wall of the colorimeter seat. After calibrating the instrument several times in a row, the sample to be tested was pushed into the optical path to measure the visible light transmittance of the sample; the tensile strength and trouser-type tear strength were measured using the UN-7001-LS servo universal material tensile testing machine of High-speed Railway Testing Instrument Co., Ltd. according to GB / T 528-2009 standard to measure the sample. The tensile strength test method is: place the type 2 dumbbell sample evenly on the upper and lower clamps, set the moving speed of the clamps to 500mm / min, start the test machine, and after the sample breaks, repeat the test of 3-4 groups of samples to obtain the tensile strength of the sample; the tear strength test method is: place the trouser-type tear sample evenly on the upper and lower clamps, set the moving speed of the clamps to 100mm / min, start the test machine, and after the sample breaks, repeat the test of 2-4 groups of samples to obtain the trouser-type tear strength of the sample; the Shore A hardness is measured according to GB / T531.1-2008 standard; the rebound is measured according to GB / T 1681-2009 standard; the DIN abrasion is measured according to the rotation test method in GB / T 9867-2008 standard; the hydrolysis resistance is measured according to QB / T The constant temperature and humidity hydrolysis resistance method in the 4671-2014 standard was used to perform a wet heat treatment on the sample. The test conditions were: test temperature 70°C, relative humidity 95%, and after continuous wet heat treatment for 168 hours, the sample was taken out and placed at room temperature for 2 hours before mechanical property testing. The hydrolysis performance retention rate before and after treatment was calculated. The performance test results of Examples 1-8 and Comparative Examples 1-5 are shown in Tables 1 and 2.
[0113] Table 1 Performance test results of Examples 1-8
[0114]
[0115] Table 2 Performance test results of comparative examples 1-5
[0116]
[0117] Table 1 and Table 2 are performance test results of products prepared by Examples 1-8 and Comparative Examples 1-5 of the present invention. Comparing Comparative Example 1 with Example 5, it is found that the performance of the products prepared by using TDI is low, and the main reason is the influence of the molecular structure of the isocyanate itself. Compared with TDI, PPDI is an aromatic diisocyanate with strong crystallinity, highly regular and symmetrical molecular structure. This unique molecular structure not only greatly improves the wear resistance of polyurethane protective materials, but also the chemical crosslinking formed by its combination with small molecule polyols enhances the interaction between molecular chains, thereby greatly improving the mechanical properties of the product; in addition, the reaction activity of PPDI is higher than that of TDI, and the reaction temperature required for preparing prepolymers with the same isocyanate content is lower, and the reaction cycle is shorter, which also reduces the reaction cycle and energy consumption to a certain extent, saving production costs.
[0118] Comparative Example 2 Compared with Example 6, after the PE-4010 polyester polyol in component A is replaced with PE-2010 polyester polyol, the product rebound is significantly reduced. This is because compared with PE-2010 prepared from a polyol with a carbon number of 2 and adipic acid, PE-4010 is prepared from a polyol with a carbon number ≥ 4 and adipic acid, and has more methylene groups, longer fat chains, lower ester density, better molecular chain flexibility, and stronger mobility. The prepared product exhibits higher resilience when subjected to impact. At the same time, due to lower crystallinity and better low-temperature resistance, the material also has better flexibility in winter.
[0119] Comparative Example 3 Compared with Example 4, after the TMP small molecule polyol in component A is replaced with 1,4-butanediol (BDO), although the product performance is improved, the light transmittance decreases significantly. This is because the functionality of BDO is lower than that of TMP, and the molecular structure of TMP contains three hydroxyl groups and three methyl groups, and the reaction activity and cross-linking degree are higher than BDO, thereby improving the transparency of the product.
[0120] Comparing Comparative Example 4 with Example 2, it is found that after replacing PE-2520 in component B with PE-2020, although the product has slightly improved in terms of abrasion, tensile strength and tear strength performance, the product transparency is significantly reduced. In Example 2, a small molecule alcohol with a higher degree of crosslinking of side methyl side chains is used as a chain extender in the product system to hinder the formation of crystallization and improve the transparency of the product. At the same time, a liquid polyester polyol PE-2520 with relatively weak crystallinity is used to react with PPDI, neutralizing the high crystallinity brought by the compact, regular and symmetrical molecular structure of PPDI, and further improving the mechanical properties of the product on the basis of ensuring the transparency and resilience of the product; compared with PE-2520, PE-2020 is solid at room temperature and has strong crystallinity. It reacts with PPDI with the same high crystallinity to improve the mechanical properties of the product, but its high crystallinity causes the product to lose the transparency brought by the small molecule polyol.
[0121] The biggest difference between Comparative Example 5 and Example 3 is that the polymer component does not contain the anti-hydrolysis agent HyMax ® 1010 component, anti-hydrolysis agent HyMax ® 1010 is a monomeric carbodiimide additive, which mainly consumes trace acids in the system to generate stable ureides, inhibiting the continued hydrolysis, thereby improving the hydrolysis resistance of the product. It itself does not participate in the system reaction, so the introduction of anti-hydrolysis agents greatly improves the hydrolysis resistance of the system without affecting the mechanical properties of the product.
[0122] It can be found from Comparative Examples 1-5 that the five groups of experimental hydrolysis performance retention rate data are all decreased to varying degrees compared with Examples 1-8. This is because for the system in the present invention, firstly, component A uses polyester polyols with lower ester bond density. The ester bonds contained in the polyester polyols are easily reacted with water under the action of the terminal carboxyl groups, resulting in the breakage of the molecular bonds. The use of polyester polyols with low ester bond density reduces the hydrolysis reaction between the ester bonds and water, thereby maintaining the stability of the molecular chain and the performance of the product; secondly, a small molecule polyol containing a higher crosslinking degree of side methyl side chains is selected in component A. The side methyl groups have strong hydrophobicity, and the introduction of side groups can hinder the OH - Attack ester group, and steric hindrance makes OH - It is not easy to attack the carbonyl group and the ester bond is not easy to break, thereby maintaining the mechanical properties of the product; thirdly, the diisocyanate component selected in component B is PPDI, which has good regularity of molecular structure and high polarity, and water molecules are not easy to enter the structure, thereby improving the hydrolysis resistance of the product; different from general polyester products, the present invention improves the hydrolysis resistance of the product under the synergistic effect of multiple specific components while introducing an anti-hydrolysis agent, further ensuring the stability of the product's hydrolysis performance.
Claims
1. A high-transmittance and high-performance polyurethane protective material, characterized in that: It is composed of component A and component B in a mass ratio of 100:(128-247), wherein component A includes the following raw materials in mass parts: 90.7-95.8 parts of polyester polyol 1, 2.2-7.3 parts of small molecule polyol, 0.5-1.3 parts of catalyst, 0.2-0.6 parts of anti-hydrolysis agent, and 0.4-0.8 parts of anti-aging agent; Component B includes the following raw materials in parts by mass: 78.8-83.4 parts of polyester polyol 2, 16.6-21.2 parts of diisocyanate; The polyester polyol 1 has a moisture content of ≤0.03%, and is selected from one or two of PE-4010 with a number average molecular weight of 1000 produced by Shandong Yinuowei Polyurethane Co., Ltd., PE-6010 with a number average molecular weight of 1000 produced by Shandong Yinuowei Polyurethane Co., Ltd., and PE-4020 with a number average molecular weight of 2000 produced by Shandong Yinuowei Polyurethane Co., Ltd.; The small molecule polyol is one or two of INOVOLC304 with a number average molecular weight of 375 produced by Shandong Yinuowei New Materials Co., Ltd., trimethylolpropane, and trimethylolethane; The polyester polyol 2 is a liquid polyester polyol with a moisture content of ≤0.03%, selected from one or two of PE-2420 with a number average molecular weight of 2000 produced by Shandong Yinuowei Polyurethane Co., Ltd., PE-2415 with a number average molecular weight of 1500 produced by Shandong Yinuowei Polyurethane Co., Ltd., and PE-2520 with a number average molecular weight of 2000 produced by Shandong Yinuowei Polyurethane Co., Ltd.; The diisocyanate is p-phenylene diisocyanate; The preparation process of component B is as follows: polyester polyol 2 is put into a reaction kettle, and when the temperature drops below 60°C, stirring is started, p-phenylene diisocyanate is added at one time, and then the kettle is sealed with nitrogen to maintain a slight positive pressure in the kettle, and the temperature is kept at 55-60°C for 30-40 minutes, and then the temperature is continued to react, and the temperature is raised to 75-85°C within the first 60 minutes, and the temperature is kept in this temperature range for 1-3 hours. After the reaction is completed, the vacuum degree is maintained at ≤-0.095MPa to remove bubbles, and a polyurethane prepolymer with an isocyanate content of 5.0-7.0% is prepared, namely component B.
2. The high-transmittance and high-performance polyurethane protective material according to claim 1, characterized in that: The catalyst is one or two of an organic bismuth catalyst BCAT-20A, an environmentally friendly catalyst CUCAT-RM01, and an amine catalyst DXD-07C.
3. The high-transmittance and high-performance polyurethane protective material according to claim 1, characterized in that: The anti-hydrolysis agent is HyMax ® 220. HyMax ® One or both of 1010.
4. The high-transmittance and high-performance polyurethane protective material according to claim 1, characterized in that: The anti-aging agents are CHISORB 971 and Sunok ® 1076A mixture in any proportion.
5. A method for preparing the high-transmittance and high-performance polyurethane protective material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Component A: Evenly mix polyester polyol 1, small molecule polyol, catalyst, anti-hydrolysis agent and anti-aging agent at 40-60°C to obtain component A; (2) Component B: Add polyester polyol 2 into a reaction kettle. When the temperature drops below 60°C, start stirring, add p-phenylene diisocyanate all at once, and then seal the kettle with nitrogen to maintain a slight positive pressure in the kettle. Keep the temperature at 55-60°C for 30-40 minutes, then continue to heat the reaction. In the first 60 minutes, heat to 75-85°C and keep it in this temperature range for 1-3 hours. After the reaction is completed, maintain a vacuum degree of ≤-0.095MPa to remove bubbles, and prepare a polyurethane prepolymer with an isocyanate content of 5.0-7.0%, i.e., component B. (3) When in use, the temperature is controlled at 60-80°C, component A and component B are mixed evenly according to the mass ratio, poured into a mold at 70-85°C, the mold is opened for 10-15 minutes, and placed at room temperature for 12-16 hours to obtain a high-transmittance and high-performance polyurethane protective material.
6. An application of the high-transmittance and high-performance polyurethane protective material according to any one of claims 1 to 4, characterized in that: Apply it to the sole protection material.
Citation Information
Patent Citations
Low-temperature-resistant and dirt-resistant polyurethane sole resin as well as preparation method and application thereof
CN117106154A
Elastomer material for shoe sole and preparation method of elastomer material
CN118165209A
Transparent polyurethane composite material as well as preparation method and application thereof
CN115746245A
Light-permeable material
JP2018104626A